Engaged Mathematics Learning as/for a Transformative Praxis - Lamichhane, Basanta Raj; Dahal, Niroj (Mathematics Education Forum Chitwan, 2021)
Engaged learning in mathematics is essential to students' success and has a significant role in creating a transformative path in mathematics education. Considering this, this editorial attempts to highlight the role of behavioural, cognitive, affective and agentic aspects of engaged learning. It is impossible to bring all aspects of this complex and multidimensional construct in this short editorial; however, we try to open a new avenue by bringing the issue of engaged learning into pedagogical practices of mathematics in the context of Nepal. The discourse opens up how disengaged learning creates a mathematical Othering and its detrimental effects on mathematics education. Moreover, this discourse binds with the major features of classroom engagement, conceptualize and the impact of engaged learning on students' success. The editorial ends with a brief overview of the issue.